Hub-organized parallel circuits of central circadian pacemaker neurons for visual photoentrainment in Drosophila. Issue 1 (December 2018) - Li, Meng-Tong; Cao, Li-Hui; Xiao, Na; Tang, Min; Deng, Bowen; Yang, Tian; Yoshii, Taishi; Luo, Dong-Gen
Abstract Circadian rhythms are orchestrated by a master clock that emerges from a network of circadian pacemaker neurons. The master clock is synchronized to external light/dark cycles through photoentrainment, but the circuit mechanisms underlying visual photoentrainment remain largely unknown. Here, we report thatDrosophila has eye-mediated photoentrainment via a parallel pacemaker neuron organization. Patch-clamp recordings of central circadian pacemaker neurons reveal that light excites most of them independently of one another. We also show that light-responding pacemaker neurons send their dendrites to a neuropil called accessary medulla (aMe), where they make monosynaptic connections with Hofbauer–Buchner eyelet photoreceptors and interneurons that transmit compound-eye signals. Laser ablation of aMe and eye removal both abolish light responses of circadian pacemaker neurons, revealing aMe as a hub to channel eye inputs to central circadian clock. Taken together, we demonstrate that the central clock receives eye inputs via hub-organized parallel circuits inDrosophila . The central circadian clock inDrosophila is made up of ~ 150 anatomically distributed neurons; the circuits underlying photoentrainment is unclear. This study describes ex vivo patch-clamp recording of the eye-mediated light response of all known circadian clock neurons, and shows that they are organized in parallel circuits centered around a hub.